Endothelial Agrin Is Dispensable for Normal and Tumor Angiogenesis - Ye, Peng; Fu, Zelong; Chung, Jeff Yat-Fai; Cao, Xiaoyun; Ko, Ho; Tian, Xiao Yu; Tang, Patrick Ming-Kuen; Lui, Kathy O. (Frontiers in Cardiovascular Medicine, 2022)
Recently, the extracellular matrix protein agrin has been reported to promote tumor angiogenesis that supports tumorigenesis and metastasis; however, there is a lack of genetic evidence in vivo to prove whether agrin derived from the tumors or endothelial cells (ECs) systemically should be the therapeutic target. To date, the physiological role of endothelial agrin has also not been investigated. In the EC specific agrin knockout mice, we observed normal endothelial and haematopoietic cell development during embryogenesis. Moreover, these mice develop normal vascular barrier integrity and vasoreactivity at the adult stage. Importantly, the growth of localized or metastatic cancer cells was not affected after implantation into endothelial agrin depleted mice. Mechanistically, agrin did not regulate endothelial ERK1/2 or YAP activation in vivo that is central to endothelial proliferation and invasion. Cumulatively, our findings may suggest that agrin could play a redundant role in endothelial development during physiological and tumor angiogenesis. Targeting the endothelial derived agrin might not be effective in inhibiting tumor angiogenesis.